Eosinophil granule proteins ECP and EPX as markers for a potential early-stage inflammatory lesion in female genital schistosomiasis (FGS). - Charles Emile Ramarokoto; Anna Overgaard Kildemoes; Bodo Sahondra Randrianasolo; Pascaline Ravoniarimbinina; Vololomboahangy Elisabeth Ravaoalimalala; Peter Leutscher; Eyrun Floerecke Kjetland; Birgitte Jyding Vennervald (PLoS Neglected Tropical Diseases, 2014)
Background Genital granulomas induced by Schistosoma haematobium eggs can manifest as different lesion types visible by colposcopy; rubbery papules (RP), homogenous sandy patches (HSP) and grainy sandy patches (GSP). Pronounced tissue eosinophilia is a candidate marker for active S. haematobium pathology, as viable schistosome egg granulomas often are eosinophil rich. Here it was investigated whether eosinophil granule proteins ECP (eosinophil cationic protein) and EPX (eosinophil protein-X) in urine and genital lavage can be used as markers for active FGS lesions. Methods Uro-genital samples from 118 Malagasy women were analysed for ECP and EPX by standard sandwich avidin/biotin amplified ELISA. Principal findings The women with RP lesions had significantly higher levels of ECP and EPX in both lavage and urine. Furthermore, women with RP lesions were significantly younger than those with GSP. This could indicate that RP lesions might be more recently established and thus represent an earlier inflammatory lesion stage. Conclusion ECP in genital lavage might be a future tool aiding the identification of FGS pathology at a stage where reversibility remains a possibility following praziquantel treatment.